Long-term observational, non-randomized study of enzyme replacement therapy in late-onset glycogenosis type II. - Bembi, Bruno; Pisa, Federica Edith; Confalonieri, Marco; Ciana, Giovanni; Fiumara, Agata; Parini, Rossella; Rigoldi, Miriam; Moglia, Arrigo; Costa, Alfredo; Carlucci, Annalisa; Danesino, Cesare; Pittis, Maria Gabriela; et al. (J Inherit Metab Dis, 2010)
OBJECTIVES: Type II glycogenosis (GSDII) is a lysosomal storage disorder due to acid alpha-glucosidase (GAA) deficiency. Enzyme replacement therapy (ERT) with human recombinant alpha-glucosidase (rhGAA) has been demonstrated to be effective in the treatment of infantile forms of GSDII, but little information is available concerning late-onset phenotypes. Long-term follow-up studies are not available at present. The aim of this study was to evaluate the ERT long-term effects in late-onset GSDII. METHODS: Twenty-four patients, including 7 juveniles and 17 adults, received bi-weekly infusion of rhGAA (20 mg/kg) for at least 36 months. Clinical conditions, muscular function (6-min walking test, 6MWT; Walton scale, WS), respiratory function (vital capacity, VC; forced expiratory volume, FEV1; arterial pCO(2)), and muscle enzymes were assessed every 6 months. RESULTS: The 6MWT improved in both juvenile and adult patients (p = 0.01, p = 0.0002, respectively), as well as in patients with moderate to severe muscle function impairment (WS >3.5; p = 0.002). An overall improvement in WS was also observed (p = 0.0003). VC and FEV1 remained unchanged, while pCO(2) decreased (p = 0.017). Muscle enzymes decreased significantly (p < 0.0001). Two patients (8%) showed transient secondary events during ERT. CONCLUSIONS: Long-term ERT with rhGAA was shown to be safe, well tolerated, and effective in improving motor function and in stabilizing respiratory function in late-onset GSDII. The response pattern showed a progressive clinical improvement during the follow-up period in juvenile patients, while in adults it reached and maintained a plateau after the first year of treatment.
Keywords: Adolescent; Adult; Age of Onset; Aged; alpha-Glucosidases; Child; Enzyme Replacement Therapy; Female; Follow-Up Studies; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Observation; Time Factors; Treatment Outcome; Young Adult